2017
DOI: 10.3892/mmr.2017.6276
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3/VDR attenuates high glucose-induced epithelial-mesenchymal transition in human peritoneal mesothelial cells via the TGFβ/Smad3 pathway

Abstract: Epithelial-mesenchymal transition (EMT) has been recognized to accelerate peritoneal membrane dysfunction. 1,25(OH)2D3/vitamin D receptor (VDR) is important for preventing various types of EMT in vivo. However, its function on EMT and inflammation of human peritoneal mesothelial cells (HPMCs) remains to be elucidated. Therefore, the present study investigated the effects of 1,25(OH)2D3/VDR on high glucose (HG)‑induced EMT and inflammation in HPMCs and the underlying molecular mechanism. It was determined that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
(25 reference statements)
2
12
0
1
Order By: Relevance
“…Vitamin D analogs can suppress matrix-producing myofibroblast activation by upregulating the expression of anti-fibrotic hepatocyte growth factor in renal interstitial fibroblasts [ 123 ]. In human peritoneal mesothelial cells, inhibitory effects of VDR agonists on EMT have also been reported [ 124 , 125 ].…”
Section: Renoprotective Mechanisms Of Vdrmentioning
confidence: 99%
“…Vitamin D analogs can suppress matrix-producing myofibroblast activation by upregulating the expression of anti-fibrotic hepatocyte growth factor in renal interstitial fibroblasts [ 123 ]. In human peritoneal mesothelial cells, inhibitory effects of VDR agonists on EMT have also been reported [ 124 , 125 ].…”
Section: Renoprotective Mechanisms Of Vdrmentioning
confidence: 99%
“…However, long-term exposure of the peritoneal membrane to nonbiocompatible peritoneal dialysis fluid, including high concentrations of glucose and lactate, glucose degradation products (GDPs), and low pH, can result in functional and structural abnormalities of peritoneum, eventually leading to the PD failure [1]. High glucose can lead to inflammation and peritoneal fibrosis (PF) [2], increase the expression of transforming growth factor-β1 (TGF-β1) [3], and stimulate a complex process of peritoneal epithelialmesenchymal transition (EMT) in vivo [4]. EMT of mesothelial cells is an reversible process in which epithelial cells transdifferentiate into cells with mesenchymal characteristics, is widely considered to be a crucial process in fibrosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that dencichine could ameliorate kidney injury in induced type II DN via the TGF-β/Smad signaling pathway and 1,25(OH)2D3/VDR could attenuate HG-induced epithelial-mesenchymal transition in human peritoneal mesothelial cells via the TGF-β/Smad3 pathway (13,14). The present study aimed to determine whether the TGF-β/Smad signaling pathway is involved in the regulation of Rg on the HG-affected cell apoptosis and proliferation.…”
Section: Rg Inhibits Hg -Induced Apoptosis and Promotesmentioning
confidence: 89%